Early Engagement of Parietal Cortex for Subtraction Solving Predicts Longitudinal Gains in Behavioral Fluency in Children - Suárez-Pellicioni, Macarena; Berteletti, Ilaria; Booth, James R. (Frontiers in Human Neuroscience, 2020)
There is debate in the literature regarding how single-digit subtraction fluency is achieved over development. While the Fact-retrieval hypothesis suggests that subtractions are solved by verbally retrieving the solution from long-term memory, the Schema-based hypothesis claims that subtractions are solved through quantity procedures that become automatic. To test these hypotheses, a sample of 46 typically developing children underwent functional magnetic resonance imaging (fMRI) when they were 11 years old (time 1), and 2 years later (time 2). We independently defined regions of interest (ROIs) involved in verbal and quantity processing using a rhyming judgment task and a numerosity localizer task, respectively. The verbal ROIs consisted of left middle/superior temporal gyri (MTG/STG) and left inferior frontal gyrus (IFG), whereas the quantity ROIs consisted of bilateral inferior/superior parietal lobules (IPL/SPL) and bilateral middle frontal gyri (MFG)/right IFG. Participants also solved a single-digit subtraction task in the scanner. We defined the extent to which children relied on verbal vs. quantity mechanisms by selecting the 100 voxels showing maximal activation at time 1 from the ROIs, separately for small and large subtractions. Results revealed that children who showed improvement in behavioral fluency from time 1 to time 2 showed a larger neural problem size effect in bilateral parietal cortex at time 1, regardless of age. These effects were driven by greater activation for the large subtractions. We then studied how activation in our ROIs changed over time. We found that improvers decreased activation for large subtractions in both parietal and frontal regions implicated in quantity, whereas non-improvers maintained similar levels of activation. The greater parietal activation for large subtractions at time 1 and their reduction in activation over time for the improvers is consistent with the Schema-based hypothesis which argues for more automatic quantity procedures with increasing skill. We also found that all children, regardless of improvement, showed decreased activation over time for large subtractions in verbal regions. The lack of a problem size effect at time 1 in verbal regions and the overall decrease from time 1 to time 2 is not consistent with the Fact-retrieval hypotheses.